Beyond participation: Welfare effects of gender-differentiated group-based approaches under climate change in Kenya - Ngigi, Marther W.; Mueller, Ulrike (My University, 2018)
A gender-differentiated data collection approach is an essential step toward understanding gendered perspectives in climate change research. Innovative institutions like group-based approaches provide opportunities to improve socio-economic, political or environmental situations with positive outcomes in the midst of climate change. However, little is known on the potential of gender-differentiated group-based approaches in the context of improving men’s and women’s welfare outcomes under climate risk. The study shows that husbands and wives associate in different groups, hence acquire different gendered benefits. Econometric analysis shows that participation in group-based approaches is influenced by both gender-specific factors such as level of education, perception of climate change and institutional factors, which in turn influence welfare outcomes of participating in social groups. In the wake of climate change, innovative institutions present important pathways to strengthen the ability of men and women to manage risks and improve their welfare. Hence, there is a need for enabling policies that nurture social capital and group-based approaches at the local level
Keywords: Gender-differentiated group-based approaches; Intra-household analysis; Welfare outcomes; Climate change; Kenya